The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/jmri.20785
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between diffusion in lumbar intervertebral disks and lumbar artery status: Evaluation with fresh blood imaging technique

Abstract: Purpose:To evaluate the correlation of the lumbar artery status with the diffusion values in lumbar vertebral disks in patients with low back problems using a fresh blood imaging (FBI) technique. Materials and Methods:First, both digital subtraction angiography (DSA) and MR angiography (MRA) was performed, and the weighted kappa value between DSA and MR angiography in evaluating the status of lumbar arteries was calculated. Then, The sagittal diffusion-weighted MR images in 260 intervertebral disks (L1-2 to L4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…16,34,35 In the normal IVD the sensory nerve fibers 16,35,88 and their accompanying blood vessels 112 are most dense posteriorly and anterior-laterally but are generally observed only to a depth of 3.5 mm from the periphery of the annulus. Interestingly, sensory information from these nerves travels in the sinuvertebral nerve to the spinal cord via 2 possible routes: segmentally through the adjacent dorsal root or extrasegmentally through the paravertebral sympathetic chain.…”
Section: The 4 Tissue Layersmentioning
confidence: 99%
“…16,34,35 In the normal IVD the sensory nerve fibers 16,35,88 and their accompanying blood vessels 112 are most dense posteriorly and anterior-laterally but are generally observed only to a depth of 3.5 mm from the periphery of the annulus. Interestingly, sensory information from these nerves travels in the sinuvertebral nerve to the spinal cord via 2 possible routes: segmentally through the adjacent dorsal root or extrasegmentally through the paravertebral sympathetic chain.…”
Section: The 4 Tissue Layersmentioning
confidence: 99%
“…Narrowing of the lumbar arteries has been shown to associate with degenerative changes in the disc [6][7][8], which may indicate that reduced blood flow due to atherosclerotic changes is interfering nutrient supply. Likewise, a previous study showed that enhancement of disc is modified by defects in the endplate [3] suggesting that the endplate has an important role in regulating the flow of nutrients into the disc.…”
Section: Introductionmentioning
confidence: 98%
“…2,8,31,63 Diffusion pathways are also strongly influenced by the presence, density, and orientation of tissue barriers such as membranes, collagen fibers, or solid tissues. 30,67,69 Because musculoskeletal tissues have substantial differences in their composition, such as the density of collagen fibers, the location of membranes, and the concentration of blood vessels, there is a wide variation in the diffusion of water between and within these tissues. 8,74 For example, subcutaneous fat cells are tightly packed and have low quantities of free water.…”
Section: Diffusion Of Water As a Clinically Important Measure Dmentioning
confidence: 99%
“…3,17,38,39 Over the course of a lifetime, the intervertebral discs often undergo substantial destructive changes, leading to a loss of water within their nuclear and annular components. 3,67,69 This condition, known as degenerative disc disease, is generally believed to be directly or indirectly involved in the generation of spinal pain for many patients; however, the mechanisms by which pain is generated remain unclear. 3,10,20,44,65 Recent studies using DWI to study the relationship of diffusion within normal and degenerative discs yield some interesting observations.…”
Section: Lumbar Degenerative Disc Diseasementioning
confidence: 99%